Some methodological reflections on oral history in the borderlands - Lampe, Urška (Acta Histriae, 2023)
The article proposes some methodological reflections on doing oral history in borderland areas, starting from the case study of the Slovene-Italian borderland. It elaborates on some mistakes and difficulties the author has faced when conducting interviews in the Slovene-Italian borderland. She reflects on various challenges and obstacles, from language to terminology and conflicting collective narratives. She concludes that, as in any oral history project, as well as in borderland areas, it is important to create a relaxed atmosphere that allows for an open discussion of issues of the shared past. In a space often full of conflicting narratives and memories this is not always easy, and it is probably easier for those who are several generations distant from the events. However, the key elements of such an interview are creating an atmosphere of mutual respect and honesty and especially to (patiently) listen to the narrator, without judgement.
Keywords: border history; borderlands; collective memory; contested past; kolektivni spomin; nasprotujoča si preteklost; obmejna območja; oral history; practices of memory; slovene historiography; Slovene-Italian border; slovensko zgodovinopisje; slovensko-italijanska meja; spominske prakse; ustna zgodovina; zgodovina meje